2009
DOI: 10.1128/aem.00036-09
|View full text |Cite
|
Sign up to set email alerts
|

Development of an mlrA Gene-Directed TaqMan PCR Assay for Quantitative Assessment of Microcystin-Degrading Bacteria within Water Treatment Plant Sand Filter Biofilms

Abstract: We report for the first time a quantitative mlrA gene-directed TaqMan PCR assay for the rapid detection of microcystin-degrading bacteria. This was applied, in combination with 16S ribosomal DNA-directed quantitative PCR and denaturing gradient gel electrophoresis, to study virgin sand filter column biofilm development and to correlate mlrA gene abundance with microcystin removal efficiency.It has been predicted that the changing climatic conditions around the world are likely to increase both the occurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
5
37
1
Order By: Relevance
“…3b, the increase of mlrA gene copy number to beyond 10 6.00 copies g À1 biofilm triggered much more rapid biodegradation, and the maximal rate cooccurred with the peak of mlrA gene abundance in October. This observation suggested that the seasonal variation in MCLR-biodegradability of biofilms on BTF was largely dependent on the dynamics in indigenous MC-degraders population, agreeing with the findings proposed previously (Ho et al, 2010;Hoefel et al, 2009). In addition, the enhanced biodegradation might be involved in MC-degrading enzyme activity, aside from MC-degrader population.…”
Section: Seasonal Variation In Mc-degrader Abundance Within Biofilms supporting
confidence: 92%
“…3b, the increase of mlrA gene copy number to beyond 10 6.00 copies g À1 biofilm triggered much more rapid biodegradation, and the maximal rate cooccurred with the peak of mlrA gene abundance in October. This observation suggested that the seasonal variation in MCLR-biodegradability of biofilms on BTF was largely dependent on the dynamics in indigenous MC-degraders population, agreeing with the findings proposed previously (Ho et al, 2010;Hoefel et al, 2009). In addition, the enhanced biodegradation might be involved in MC-degrading enzyme activity, aside from MC-degrader population.…”
Section: Seasonal Variation In Mc-degrader Abundance Within Biofilms supporting
confidence: 92%
“…Previous studies proposed that MCs are used as secondary substrates by MC-degrading bacteria that come into contact with them (17,22). Microorganisms accumulate in polysaccharide matrices and form structural and functional microbial assemblies on surfaces submerged in water commonly known as biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the abundance of total Microcystis spp., toxic Microcystis spp., and MC-degrading bacteria in Dianchi Lake, a qPCR assay was performed using primers based on 16S rRNA genes, mcyD genes, and mlrA genes, according to previously described methods (6,9,22). Microcystis aeruginosa PCC7806 was used as the standard strain for the quantification of both total Microcystis spp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations